Transferência de oxigênio e cisalhamento em biorreator convencional com diferentes combinações de impelidores - Buffo, Mariane Molina (Universidade Federal de São Carlos, 2016)
The type and operational conditions of a bioreactor chosen during the production phase of a product of interest affect not only the morphology and growth of filamentous microorganisms but also the product itself. Still the most common process to produce bioproducts is submerged cultures in conventional stirred and aerated bioreactors, with impeller of type six flat-blade turbine, or Rushton turbine (RT), which promotes good mixing and suitable oxygen transfer, but its power consumption is high and it causes high shear rate to the broth creating a hostile environment to the microorganisms. Alternatively, an impeller of the type “Elephant Ear” (EE) is shown in the literature as a “low shear” impeller, more suitable for the cultivation of shear sensitive microorganisms. This impeller creates a mixed flow (axial and radial) of broth with down flow (EEDP) or up (EEUP) depending on its geometry. This study aimed to evaluate the best association of impellers for filamentous fungi cultures in a conventional bioreactor. Initially the volumetric coefficient of oxygen transfer (kLa) and the power consumption of seven different association of impellers were evaluated. The results obtained the factorial design methodology showed that the associations EEDP-EEUP, RT-EEDP, and EEDP-RT, showed the best results regarding the oxygen transfer and the power consumption, being up to 87% more efficient than the standard RT-RT association. Two of the better performing association and the traditional (RT-RT) were selected to be evaluated regarding the shearing, by using empirical equations and the size of the eddies, evaluated by the Kolmogorov microscale. The association that showed higher values on the Kolmogorov scale and least shearing was EEDPEEUP, with shearing up to 60% lower than the RT-RT association. In the last step the effects of shear on the morphology of the fungi Aspergillus niger was evaluated. Short-term cultures (4h) were cultivated so that the cellular growth would not harm the analysis. The results showed that on the culture that used the EEDP-EEUP association the morphological form of cell clumps predominated, while on the culture that used the RT-RT association the morphological form of branched hyphae predominated, suggesting that the RT-RT association causes more shearing and can cause irreversible damage to the fungal cells.
Keywords: Associações de impelidores; Impelidor orelha de elefante; Turbina Rushton; Transferência de oxigênio; Consumo de potência; Cisalhamento; Aspergillus niger; Impellers associations; Elephant ear impeller; Rushton turbine; Oxygen transfer; Power consumption; Shear; Aspergillus niger; CIENCIAS EXATAS E DA TERRA